Exercise Decreases Risk of Future Active Disease in Inflammatory Bowel Disease Patients in Remission - Jones, Patricia D. (Inflamm Bowel Dis, 2015)
BACKGROUND: Although exercise impacts quality of life in patients with inflammatory bowel disease (IBD), little is known about its role in disease activity. Among IBD patients in remission, we aimed to evaluate the association between exercise and subsequent active disease. METHODS: We performed a prospective study using the Crohn's and Colitis Foundation of America (CCFA) Partners Internet-based cohort of individuals with self-reported IBD. We identified participants in remission, defined as short Crohn's disease activity index (sCDAI) <150 or simple clinical colitis activity index (SCCAI) ≤2. The primary exposure was exercise status, measured using the validated Godin leisure time activity index. The primary study outcome, assessed after six months, was active disease defined using the above disease activity index thresholds. We used bivariate and multivariate analyses to describe the independent association between exercise and risk of active disease. RESULTS: We identified 1308 patients with Crohn's Disease (CD) and 549 with ulcerative or indeterminate colitis (UC/IC) in remission, of whom 227(17.4%) with CD and 135 (24.6%) with UC/IC developed active disease after 6 months. Higher exercise level was associated with decreased risk of active disease for CD (adjusted RR 0.72, 95% CI 0.55-0.94) and UC/IC (adjusted RR 0.78, 95% CI 0.54-1.13). CONCLUSIONS: In patients with CD in remission, those with higher exercise levels were significantly less likely to develop active disease at six months. In patients with UC/IC in remission, patients with higher exercise levels were less likely to develop active disease at six months, however this was not statistically significant.